EFEKTIFITAS PROGRAM PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DESA (P3MD) DI DESA HUTAURUK HASUNDUTAN KECAMATAN SIPOHOLON KABUPATEN TAPANULI UTARA TAHUN 2020 - Aldi Hutauruk; Husni Thamrin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
Village Community Development and Empowerment (P3MD) is an effort to develop community independence and welfare by increasing knowledge, attitudes, skills, behavior, abilities, awareness, and utilizing resources through the establishment of policies, programs, activities and assistance in accordance with the essence of the problem and priority needs. villagers. Village development is a process of development activities that take place in the village which covers all aspects of community life and livelihood. Empowerment is an effort carried out to improve the ability of the community to be more able to meet their needs and be more involved in the decision-making process on an equal basis with others. The purpose of this study was to find out how the Effectiveness of the Village Community Development and Empowerment Program in Hutauruk Hasundutan Village, Sipoholon District, North Tapanuli Regency in 2020. This type of research is a qualitative research using a descriptive approach. This research was conducted in Hutauruk Hasundutan Village, Sipoholon District, North Tapanuli Regency. The effectiveness that can be seen from the Hutauruk Hasundutan Village Community Development and Empowerment Program carried out is Development and Empowerment that has been carried out to the Community, Development and Empowerment has been carried out which aims to support all existing needs in the community such as inadequate development, community development and assistance. - Assistance provided to the community. All programs carried out aim to improve the welfare of the people of Hutauruk Hasundutan Village.